The Detrimental Effect of Machiavellian Leadership on Employees’ Emotional Exhaustion: Organizational Cynicism as a Mediator - Gkorezis, Panagiotis (Eur J Psychol, 2015)
Numerous empirical studies have examined predictors of emotional exhaustion. In this vein, both positive and negative leadership styles have been associated with this outcome. Yet, little is known about the role of Machiavellian leadership in fostering employees’ emotional exhaustion. As such, we investigated the relationship between Machiavellian leadership and emotional exhaustion. Even more, we investigated an explanatory mechanism of this association by encompassing organizational cynicism as a mediator. Results showed that Machiavellian leadership has a both direct and indirect, through organizational cynicism, on employees’ emotional exhaustion.